Antibacterial Activity of Lemongrass-Scented Betel Herbal Tea - Akma Suhaimi, Mazaitul; Ho, Lee-Hoon; Tang, John-Yew-Huat; Ain Mustafa, Kamarul ‘ (International Journal of Engineering and Technology, 2018)
Betel (Piper betle) and lemongrass (Cymbopogon citratus) are well known medicinal plant that exhibit good antimicrobial properties. This study aims to investigate antibacterial potency of Lemongrass-Scented Betel Tea (LSBT). Four herbal infusions formulations (B-100:L-0, B-95:L-5, B-85:L-15 and B-75:L-25) with different percentage of betel leaves and lemongrass stem powder were prepared. These herbal infusions were tested against four foodborne pathogens, which are Staphylococcus aureus (ATCC 29213 and ATCC 33591) (Gram-positive cocci) and Escherichia coli (ATCC 25922 and ATCC 35218) (Gram negative bacteria) using Kirby-Bauer disk diffusion method. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) assays were determined by broth dilution method. B-100:L-0 showed strongest antimicrobial properties with inhibition zones of 28.5 ± 0.71 to 29.0 ± 1.41 mm and 10.0 ± 0.00 mm for S. aureus and E.coli, respectively. Moreover, B-100:L-0 infusion also showed the lowest MIC (0.63 mg/mL) and MBC (1.25 mg/mL) values for S. aureus as well as the lowest MIC (5.0 mg/mL) value for E.coli. In conclusion, all four formulations of the herbal tea showed inhibitions against S. aureus (ATCC 29213 and ATCC 33591) and E. coli (ATCC 25922 and ATCC 35218). However, Gram-negative bacteria were more resistant to antibacterial effects of the herbal tea. It can be suggested that the use of B-100:L-0 would be hepful in the treatment of infections caused by  S. aureus (ATCC 29213 and ATCC 33591) and E. coli (ATCC 25922 and ATCC 35218).